ANALISIS SANAD DAN MATAN HADIS TENTANG KEUTAMAAN BULAN RAMADAN (DIBELENGGUNYA SETAN-SETAN) - AAS ASARI (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2017)
In months Ramadan, all people struggle to keep their fasting. The governments also really pay attention to fasting activity in months Ramadan. The public phenomenon has been doing the sin in months Ramadan is the problem that should to watch. What are the people in the world doing the sin because of only devil temptation? Or are there the other factors that make the people dong the sin? The goals of this research is to obtain the data of hadis accurately about the superiority in months Ramadan (the devils handcuffed) by this hadis, is the hadist can be a hujjah or not?. After doing this research by using qualitative approach, literature method, and descriptive, also using the sanad and matan criticism theory, it can be concluded that the hadis of the months Ramadan superiority about the devils handcuff is able to the new knowledge. The hadis that explain about the superiority of months Ramadan (the devils handcuffed) the entire narrated strip based on the quality of this hadis initially include in the criteria of Sahi>h} hadis, except the hadis that narrated by Imam Al-Nasa>’i on the fourth sanad schema included in the da’if category because broken the sanad from Ubaidillah, Ya’qub, Ibrahim, Ibnu Ishaq, Ibnu Shihab, and Ibnu Abi Anas which should from Ibnu Abi Anas to Abu Anas, in this sanad strip directly to Abu Hurairah. Besides, there is a friend to jarh claimed that as suduq yudallis by Ibnu Hajar is Muhammad bin Ishaq. Although there is broke sanad strip, but this hadis reinforced with the other hadis strip such as narrated strip of Imam An-Nasai and other mukharij in order to degree of the hadis raise become s}ah}i>h} li ghairihi hadis. Meanwhile, based on the quantitiy this hadis included into ahad gharib hadis that initially affected by only one person to narrate, he is Abu Hurairah. But, quantity of the hadis is change become ahad gharib hadis because every narrator thabaqah increased. The meaning of hadis about the superiority of months Ramadan (the devils handcuffed) has two real meanings. The hadis interpreted obviously that the devils really handcuffed obviously. Second meaning is majazi which the meaning is only analogy the devils are not handcuffed, but the devils cannot disturb people that doing the fasting.